ASSESSING PARAGRAPH DEVELOPMENT OF INDONESIAN STUDENTS’ COMPOSITION BY USING CONTENT ANALYSIS - Yeni Arif Rahman (Universitas Majalengka, 2021)
Assesing students’ compositions is always a main concern of teachers. By assessing them, teachers know whether the goal of the lesson has been met. The study aims to assess paragraph development of Indonesian students’ composition. The data were 30 paragraphs collected from 10 compositions of university students from Indonesia. The study employs content analysis procedure to analyze four elements of effective paragraph: topic sentence, adequate development, unity, and coherence. The result shows that all 30 samples of paragraph contains topic sentences at the beginning of the paragraph with 14 paragraph (48%) has adequate development, 18 of them (60%) have unity in paragraph, and 16 (54 %) paragraphs contains coherence. It can be inferred that the paragraphs were partially developed so they need further polishing and development